2019
DOI: 10.3390/nano9020222
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Z-scheme Heterojunction of Egg-Like Core@shell CdS@TiO2 Photocatalyst via a Facile Reflux Method for Enhanced Photocatalytic Performance

Abstract: A well designed and accurate method of control of different shell thickness and electronic transmission in a Z-scheme core@shell system is conducive to obtaining an optimum photocatalytic performance. Herein, the Z-scheme heterojunction of egg-like core@shell CdS@TiO2photocatalysts with controlled shell thickness (13 nm, 15 nm, 17 nm, 22 nm) were synthesized by a facile reflux method, and the CdS@TiO2 structure was proved by a series of characterizations. The photodegradation ratio on methylene blue and tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 44 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…It could be concluded that more water aging time results in a thicker oxide shell because of reaction of zero valent iron with O 2 /H 2 O in the solution. The increase in shell thickness was also seen by Xue et al by preparing the core-shell nanocomposite, synthesized through the facile reflux method [17, 18].
Fig.
…”
Section: Resultsmentioning
confidence: 63%
“…It could be concluded that more water aging time results in a thicker oxide shell because of reaction of zero valent iron with O 2 /H 2 O in the solution. The increase in shell thickness was also seen by Xue et al by preparing the core-shell nanocomposite, synthesized through the facile reflux method [17, 18].
Fig.
…”
Section: Resultsmentioning
confidence: 63%
“…In comparison, photocatalysis degradation based on semiconducting materials can harness solar energy for mineralization of organic pollutants and offers advantages such as no secondary pollution, low energy consumption, and practicability. In this respect, semiconducting photocatalysts such as Ag 2 MoO 4 [10], Ag 3 PO 4 [11], BiOI [12], Bi 3 O 4 Cl [13], Bi 2 MoO 6 [14], CdS [15], g-C 3 N 4 [16], and Ag 2 Se [17] have been proposed for removing organic contaminants [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, TiO 2 -based nanostructured photocatalysts such as one-dimensional (1-D) [11,12,13], two-dimensional (2-D) [14,15,16], and three-dimensional (3-D) or hierarchical structures [17,18], have received massive attention in a variety of photocatalysis domains [19]. The distinct properties of large surface area, high aspect ratio, directional flow of photogenerated charges resulting in decreased charge recombination, light scattering, stability and improved reusability/recyclability—especially for 1-D arrays and hierarchical nanostructures—has made them valuable and worthwhile to employ in the photocatalysis research domain.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the eminent benefits of TiO 2 nanostructured photocatalysts, to some extent, they possess limitations with respect to the ultra violet region (a small portion of terrestrial solar spectrum) in terms of light absorption due to their wider band gap (~3.0–3.2 eV). Therefore, to overcome such limitations, similar strategies are commonly adopted as for 0-D nanoparticles, including metal and non-metal doping [18,22,23,24,25], noble metal loading [16,26,27,28,29], graphene derivative coupling [30,31,32,33], and hetero-junctioning TiO 2 nanostructures through the coupling of low band gap materials [11,17,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%